Barriers to halal cosmetic certification: Insights from local cosmetic producers in Brunei - Abdul Halim, Aiman Samhani; Aghwan, Zeiad Amjad (International Journal of Halal Industry, 2025)
Purpose – This study investigates the experiences and challenges encountered by local cosmetic producers in Brunei in obtaining halal certification for their products. Methodology – A qualitative research design was employed in this study, with data collected through semi-structured interviews involving eight local cosmetic producers in Brunei, all of whom were considered MSMEs. Findings – The study identifies the bottlenecks to obtaining halal certification revolving around inexpedient requirements during application, tedious approval process, costly application fee, and compressed-operating counter hours. However, the findings revealed that the challenges were not directly linked to the halal certification process itself, but rather to securing the prerequisite Cosmetic Product Notification (CPN), which is required before a halal application for cosmetics can be submitted. Implications – This study extends the understanding of the current challenges faced by local cosmetic producers, which may lead to their growth and readiness in the cosmetic industry. The results also suggest that authorities should streamline CPN requirements to enhance the growth of the halal cosmetics industry, particularly in Brunei. Further research should examine these challenges from the government’s perspective as policymakers to provide a more balanced understanding of the certification process and examine best solutions and practices from other countries with more streamlined halal certification systems. Originality – This study offers a novel contribution by examining the halal certification process for cosmetic products in Brunei from the perspective of local MSME producers, an area that has received limited scholarly attention.